(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The melody of the national instrument awakens national pride and pride in people’s hearts. We know that among the national musical instruments of the Uzbek people, the dutor instrument is of great importance in terms of performance capabilities. This article discusses the role of the dutor instrument in the performance of national instruments.